Membangun Loyalitas Pelanggan “Citilink” Garuda: Tinjauan Manajemen Hubungan Pelanggan - Prima Mulyasari Agustini (MediaTor (Jurnal Komunikasi), 2007)
Building a loyal customer community is the aim of transportation business. Citilink as one of national flag carrier manages its customer relation by maintaining communication among customer, corporate, and workforce. Using communication management approach to build a close connection among its customers, Citilink focused on 4 aspects: makes regular repeat purchase, purchases across products and service lines, refers others, and demonstratesimmunity to the pull of competition. A system of customer satisfaction fulfillment needs to be established to ensure customer loyalty.